2014
DOI: 10.1088/0004-637x/790/2/149
|View full text |Cite
|
Sign up to set email alerts
|

Very-High Energy Observations of the Galactic Center Region by Veritas in 2010-2012

Abstract: The Galactic center is an interesting region for high-energy (0.1-100 GeV) and very-high-energy (E > 100 GeV) γ-ray observations. Potential sources of GeV/TeV γ-ray emission have been suggested, e.g., the accretion of matter onto the supermassive black hole, cosmic rays from a nearby supernova remnant (e.g., Sgr A East), particle acceleration in a plerion, or the annihilation of dark matter particles. The Galactic center has been detected by EGRET and by Fermi/LAT in the MeV/GeV energy band. At TeV energies, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…The detected signal was therefore concluded to most likely be of non-dark matter origin, and limits to σ v of the order of 10 −24 -10 −23 cm 3 s −1 could be inferred. Later observations by MAGIC [23] and VERITAS [24] are in agreement with these conclusions.…”
Section: Indirect Dark Matter Searches With Cherenkov Telescopessupporting
confidence: 81%
“…The detected signal was therefore concluded to most likely be of non-dark matter origin, and limits to σ v of the order of 10 −24 -10 −23 cm 3 s −1 could be inferred. Later observations by MAGIC [23] and VERITAS [24] are in agreement with these conclusions.…”
Section: Indirect Dark Matter Searches With Cherenkov Telescopessupporting
confidence: 81%
“…The HESS, VERITAS and MAGIC Collaborations have each reported the detection of very high-energy (VHE) gamma-ray emission from the direction of the Galactic Center, extending to energies of ∼30-50 TeV [1][2][3][4][5][6][7][8]. When this emission was initially identified, it was suggested that it may originate from the Milky Way's central supermassive black hole, Sgr A * [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Galactic center is a strong and well established source of VHE γ-rays (Aharonian et al 2004, Albert et al 2006a, Archer et al 2014. It was already early suggested that the point source in the galactic centre would correspond to a central black hole (Aharonian et al 2004), but as there are also other candidates, such as supernova remnant Sgr A East, the question of direct emission of the black hole in the center of our galaxy is not yet resolved.…”
Section: Supermassive Black Hole In the Centre Of Our Galaxymentioning
confidence: 92%